PENGETAHUAN IBU TENTANG IMUNISASI DASAR BALITA - Adinda Nola Karina; Bambang Edi Warsito (Jurnal Keperawatan Diponegoro, 2012)
Immunization is one of the efforts to increase impenetrability of body and contagion eradication. The high grade of mortality child and baby in Indonesia caused decline degree of society health, one of the effort to overcome this problem is giving the basic immunization to the babies and the children completely. But this program still have problems, it is the refusal of the parents. Parental refusal of immunization is due to the incorrect assumption that developed in the community about immunization, low levels of knowledge and awareness of the lack of immunization The purpose of this research is to describe characteristics mothers’ knowledge about the basic immunization for children. This research used quantitative research, with descriptive survey design. Samples were 88 peoples taken by purposive sampling. The result of this research showed mothers who have good knowledge is 62.5% and who have less knowledge 37.5%. The conclusion of this research that most mothers have good knowledge about the basic immunization for children, and a good knowledge of this is expected to support the good immunization status for children